Creative Models of Junior High School Students in Solving Open Ended Mathematical Problems on Keirsey Personality Types - Prambudi, Saesar Adhe; Susanto, Hery; Purwanto, Purwanto (Universitas Suryakancana, 2025)
This research is based on the 21st century 6Cs skills, namely character, citizenship, critical thinking, creativity, collaboration, and communication. Student personality or more broadly, character, contributes to the variation in students’ creative outcomes. In this study, creativity is assessed through three aspects of the creative model: imitation, modification, and creation. The creative model is explored through open-ended mathematical problem-solving. This qualitative descriptive research aims to describe students’ creative models in open-ended mathematical problem-solving in relation to their Keirsey personality types. The study was conducted at MTS Negeri Kota Batu, with 4 out of 27 seventh grade students selected as research subjects using a Keirsey personality type questionnaire, which categorized them as guardian, artisan, rational, and idealist. The results indicate that the guardian subject only exhibited one aspect, namely modification, which was still at a low level. The artisan subject demonstrated moderate imitation and very low modification. The rational subject showed moderate imitation, high modification, and high creation. The idealist subject exhibited moderate imitation, moderate modification, and high creation. Based on these findings, it can be concluded that two subjects with idealist and rational personality types fulfilled all three aspects of the creative model, while the other two subjects, with artisan and guardian personality types, only fulfilled the imitation and modification aspects.